Solos de manguezais sob a influência do Semiárido cearense: Biogeoquímica de Fe, Mn, Cu, Ni e Cr - Gadelha, Fabiana Machado (2014)
Mangroves are environments with high biodiversity and are an important food source for coastal communities. However, even taking into account its great ecological value, over the past decades mangroves have suffered from anthropogenic practices. These practices often are associated with deforestation, occupation of coastal areas and installation of shrimp ponds, generating loads of metal for environments that are final recipients. With this, the aim of the present work conduct the study biogeochemical between mangroves in conservation area (ET Timonha- River estuary) and in areas affected by the provision of shrimp effluent (River Estuary Jaguaribe- EC) and of urban origin (River Estuary Cocó- EC) forms of Fe and its role through the fractionation of Fe and associated metals in different seasons. In the samples were measured pH, Eh, organic carbon content and grain size held. In addition, were subjected to sequential extractions of metals. The results indicate that the seasonal variation influenced the Fe and Mn behavior, because it is now reducing anoxic now and in the formation of iron oxyhydroxides. The Mn present in the mangroves also changed between the two periods, lingando- the fractions differentiated between the two periods. The other metals (Cu, Ni and Cr) There are influenced by seasonality.